Information about the "Pantanal Passo da Lontra" - de Paula, José Elias; Conceição, Cláudio de Almeida; Macêdo, Miramy (Pesquisa Agropecuaria Brasileira, 1995)
The Pantanal Passo da Lontra is situated at Miranda MS, Brazil, between co-ordinates 20°30'S and 56°15'W. The study covered an area of approximately 180 km2, in which some different vegetation types were observed, such as swamp or aquatic vegetation, flooded vegetation, mountain ranges forest, and small hills ("murundus") and chaco fields. This study was realized from 1989 to 1991 and an extensive collection of vegetative types was made during February, May, July, August, November and December. Seventy six species were collected and identified, from which 34 have arboreal aspects. In 1,000 m2 of inventoried forest, dry wood yield was about 61,874 tons, originating from 131 trees. Dispersal agents of fruits and seeds were also studied, and the following classes were verified: Anemochory, Artidactylochory, Autochory, Hydrochory, Ichthyochory, Chiropterochory, Ornithochory and Primatochory.